Heat flux in chains of nonlocally coupled harmonic oscillators: Mean-field limit - Defaveri, Lucianno; Olivares, Carlos; Anteneodo, Celia (Physical review. E, 2022)
We consider one-dimensional systems of all-to-all harmonically coupled particles with arbitrary masses, subject to two Langevin thermal baths. The couplings correspond to the mean-field limit of long-range interactions. Additionally, the particles can be subject to a harmonic on-site potential to break momentum conservation. Using the nonequilibrium Green's operator formalism, we calculate the transmittance, the heat flow, and local temperatures for arbitrary configurations of masses. For identical masses, we show analytically that the heat flux decays with the system size N as 1/N regardless of the conservation or not of the momentum and of the introduction or not of a Kac factor. These results describe, in good agreement, the thermal behavior of systems with small heterogeneity in the masses.